Flow unsteadiness and pressure pulsations in a nuclear reactor coolant pump - Ni, Dan (Strojniški vestnik, 2016)
Unsteady flow induced by rotor-stator interaction is detrimental to the safe operation of the nuclear reactor coolant pump, so it is essential to clarify flow structures and pressure pulsations in such pumps, especially within the spherical casing. In this paper, unsteady flow characteristics in a mixed-flow nuclear reactor coolant model pump were investigated using large-eddy simulation (LES) method. Results show that at the nominal flow rate, in two particular diffuser channels near the spherical casing discharge nozzle, the flow structures are uneven compared with that in the other flow channels. The reason is associated with the position of the flow channel with respect to the spherical casing nozzle. Large- scale flow separation and backflow structures easily occur at the regions near these two channels. In the right and the middle region of the casing nozzle, due to the large-scale separate flow and high vorticity magnitude, unsteady flow structures are more complicated in comparison with the other regions. It has been found that the vorticity spectra and the pressure spectra almost have the same main excitation frequencies. Therefore, it has been confirmed that for particular regions pressure pulsations are determined by the shedding vortex wake from the diffuser blade trailing edge of the nuclear reactor coolant model pump.
Keywords: črpalke za hladilno vodo jedrskega reaktorja; nestacionaren tok; nestacionarne tokovne strukture; obsežen ločeni tok; sferično ohišje; tlačni impulzi; vrtinčenje